2017
DOI: 10.14419/ijm.v5i2.8106
|View full text |Cite
|
Sign up to set email alerts
|

Congenital abnormalities: experiences of parents atoshakati intermediate hospital, oshana region, Namibia

Abstract: Background: Congenital abnormality (CA) is one among eminent problems in the society that affects the livelihood of the individual, communities and the health sector. It creates uncertainty among family members as they strive to identify ways and means to assist one another in the upbringing of these children born with an anomaly. The ultimate purpose of this study was to describe and explore the experiences of parents of children with congenital abnormalities and to identify the source of support such as pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
7
0
Order By: Relevance
“…Literature has shown that, the presence of a child with CP may have positive and negative influences on the relationships between families [2]. On the positive side, it can broaden horizons, increase family members' awareness of inner strength, enhance family bond and encourage networks to existing community groups [1], on the other hand, the physical, emotional demands and logistical complexities associated with raising a child with CP may have a negative effect on parents and families. Living with such a child can be a source of distress to families who might face several challenges to come to terms with the functional limitation of a child with CP.…”
Section: Impact Of Cerebral Palsy On Family Relationshipsmentioning
confidence: 99%
See 4 more Smart Citations
“…Literature has shown that, the presence of a child with CP may have positive and negative influences on the relationships between families [2]. On the positive side, it can broaden horizons, increase family members' awareness of inner strength, enhance family bond and encourage networks to existing community groups [1], on the other hand, the physical, emotional demands and logistical complexities associated with raising a child with CP may have a negative effect on parents and families. Living with such a child can be a source of distress to families who might face several challenges to come to terms with the functional limitation of a child with CP.…”
Section: Impact Of Cerebral Palsy On Family Relationshipsmentioning
confidence: 99%
“…Given the indication that some children with CP often exhibit higher rates of behavioral problems than typically developing children, the relation of behavioral problems to parental wellbeing indicates that, interventions which address the child behavioral problems should be well-thought-out [1,16]. The impact of a conflicting marriage on parental wellbeing should be well understood by trained professionals such as teacher and health care providers, who interacts with these families from time to time.…”
Section: Cerebral Palsy and Marital Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations